2000
DOI: 10.3904/kjim.2000.15.1.71
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of the High Mobility Group 1 Y mRNA in Thyroid Cancers : Useful Tool of Differential Diagnosis of Thyroid Nodules

Abstract: ObjectiveThyroid nodule is frequent and occurs in about 5% of the general population. In contrast, thyroid cancer is much less frequent and occurs in about 5–10% of thyroid nodules. Distinguishing between benign and malignant lesions is an important task that is best accomplished by fine needle aspiration. Recently, Chiappetta et al. reported that the expression of the high mobility group (HMG) I(Y) proteins correlates with the malignant phenotype of human thyroid neoplasia, and suggested that the detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…They confirmed the above observation that thyroid carcinomas expressed high levels of HMG-1(Y) mRNA compared with benign thyroid nodules and normal thyroid tissue. This provides further evidence for a correlation between the expression of HMG-1(Y) and the malignant phenotype of thyroid cancer and its potential use as a marker for thyroid cancer [55].…”
Section: Thyroid Cancermentioning
confidence: 89%
See 1 more Smart Citation
“…They confirmed the above observation that thyroid carcinomas expressed high levels of HMG-1(Y) mRNA compared with benign thyroid nodules and normal thyroid tissue. This provides further evidence for a correlation between the expression of HMG-1(Y) and the malignant phenotype of thyroid cancer and its potential use as a marker for thyroid cancer [55].…”
Section: Thyroid Cancermentioning
confidence: 89%
“…Moreover, comparison of expressed cDNAs has identified HMG-1(Y) as one of a number of genes upregulated in metastatic neoplasms as compared with primary cancers in both animals [29,31] and human [31,51]. In surgical specimens of human cancers, HMG-1(Y) expression is upregulated in neoplastic tissues compared with pathologically normal tissue in colorectal [32][33][34][35], prostate [28,53], thyroid [42,43,55], pancreatic [39,40], and cervical [36] carcinoma, with most studies reporting a correlation with the more aggressive phenotypes. There is some evidence associating HMG-1(Y) expression with breast [24,51], neuroblastic [37], and gastric [44] carcinomas, but the numbers of patients studied are very small.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…48 In thyroid cancer, high HMGA1 expression can be used as a diagnostic marker of thyroid follicular cancer to distinguish between nodular thyroid and thyroid cancer. 29 It was reported that HMGA1 has a vital role in thyroid tissue through inhibition of p53 50 and HAND1 51 and induction of TGF-β1 52 and S100A13. 53 The HMGA1P6 and HMGA1P7 also functions in promoting the malignant progression of thyroid cancer.…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…was correlated with the stage of the tumor (6,7,8,10). How.=ver, the present results indicate a differential expression of HMG I(Y) proteins even in normal tissues as a function of proliferation rate.…”
Section: Resultsmentioning
confidence: 53%